Green infrastructure in Central, Eastern and South Eastern Europe - Marot, Naja (Urbani izziv, 2015)
Green infrastructure as a concept has been introduced only lately in the frame of the sustainability and resilience approaches, and as a response to the natural disasters affecting both, urban areas and as well the country side. The analysis of scientific literature has shown that the concept of green infrastructure is most often related to the concepts of sustainability, resilience, smart cities and others. The cases, presented in the articles of this special issue, are showing that the concept of green infrastructure encompasses variety of the topics; that there is diversity in the administrative levels on which the policies and measures concerning green infrastructure can be applied and that the concept allows for a great amount of innovativeness of solutions and cross-sectoral approaches.
Keywords: climate change; green infrastructure; javni prostori; javno zdravje; klimatske spremembe; planning; public health; public space